The Effectiveness of Ustadz Hanan Attaki's Da'wah Sharing Time on Youtube - Muharrifah, Ezra; Sikumbang, Ahmad Tamrin (STAI Publisistik Thawalib Jakarta, 2025)
The pandemic has accelerated digital da'wah through social media. Ustadz Hanan Attaki has utilized this opportunity with a relaxed, engaging, relevant, and easily understood style that resonates with the younger generation. This study aims to analyze the effectiveness of Ustadz Hanan Attaki’s “sharing time” da'wah activities delivered via the YouTube social media platform. It employs a qualitative approach using the Ethnographic Content Analysis (ECA) method, involving active observation, visual content analysis, and data triangulation to ensure data validity. Findings reveal that Ustadz Hanan Attaki preaches through social media and in-person events using the Mau’izah Hasanah method, including advice, good news, moral counsel, and inspirational stories. His da'wah style is relaxed, contemporary, and highly relevant to today’s youth. Through YouTube, he addresses everyday life topics using storytelling, motivational, and empathetic approaches. His messages are easily understood, emotionally impactful, and encourage introspection and spiritual connection with Allah. Positive audience responses indicate that his digital da'wah fosters spiritual and psychological engagement. Conclusion: Ustadz Hanan Attaki’s da'wah is practical and accessible, delivered in a relaxed style that appeals to young audiences and inspires through digital media.